Characteristics of professional and non-professional football players - an eight-year follow-up of three age cohorts - Sæther, S. A. (Montenegrin Journal of Sports Science and Medicine, 2017)
Identification of the most talented youth players is regarded as a key part of the talent development process in football. The basis for the criteria is naturally affected by the characteristics of the early-detected talented players. Nonetheless, earlier research has found limited evidenced for different criteria in this process. This study has examined whether professional and non-professional football players showed differences in player and coach characteristics as talented youth-level players eight years earlier. A total of 103 players selected for Norwegian youth national teams (age cohorts 1991-1993) participated in this study. Based on player and coach characteristics, the results showed that non-professional players had the most playing time and felt more successful in comparison to the professional players. The professional players, however, reported higher ambitions and a higher number of weekly-organized training sessions. No differences between the professional and non-professional players showed in terms of their relationship to their coaches were found. The study concludes that we need more research on identification criteria to be able to predict which abilities and skills should be sought in the identification process for youth-level players. As in earlier research, this study also found a poor relationship between youth performance and senior performance